Math question ?

Attachment image

3 Answers

Relevance
  • 4 weeks ago

    f(x) = -3x + 3 

    f(-2) = 9

    • Log in to reply to the answers
  • 4 weeks ago

    Substitute x with -2.

    -3 (-2) + 3.

    -3 x (-2) = 6

    6 + 3 = 9

    f(-2) = 9

    • Log in to reply to the answers
  • Anonymous
    4 weeks ago

    Just replace x by -2 everywhere:

    f(x) = -3x + 3

    f(-2) = -3(-2) + 3

    . . . . = 6 + 3

    . . . . = 9

    • Log in to reply to the answers
Still have questions? Get answers by asking now.